Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-03-16T21:35:53+01:00
A) -9z-(4-3z)-8y-(-7z+8y)+(-2y-7) =
=-9z-4+3z-8y+7z-8y-2y-7 =
=z-11-18y

b) 3(b-5a_-2(3b+a) =
= 3(b-5a)-2(3b+a) - rozumem ze tu miał byc nawias;)
= 3b-15a-6b-2a =
= -3b-17a
2010-03-16T21:36:00+01:00
A) -9z-(4-3z)-8y-(-7z+8y)+(-2y-7)=-9z-4+3z+7z-8y-2y-7=z-11-10y


b) 3(b-5a_-2(3b+a) = 3(b-5a)-2(3b+a) = 3b-15a-6b-2a = -3b-17a
2010-03-16T21:38:38+01:00
A)-9z-3z-7z+4-7+8y-8y-2y jakbyco rozwiazania dalej -19z+(-3)+(-2y)

b)3-2+b+3b+a-5a 1+4b+ 4a